Phosphatidic acid‐mediated activation and translocation to the cell surface of sialidase NEU3, promoting signaling for cell migration. Issue 5 (12th February 2015) - Shiozaki, Kazuhiro; Takahashi, Kohta; Hosono, Masahiro; Yamaguchi, Kazunori; Hata, Keiko; Shiozaki, Momo; Bassi, Rosaria; Prinetti, Alessandro; Sonnino, Sandro; Nitta, Kazuo; Miyagi, Taeko
ABSTRACT: The plasma membrane‐associated sialidase NEU3 plays crucial roles in regulation of transmembrane signaling, and its aberrant up‐regulation in various cancers contributes to malignancy. However, it remains uncertain how NEU3 is naturally activated and locates to plasma membranes, because of its Triton X‐100 requirement for the sialidase activity in vitro and its often changing subcellular location. Among phospholipids examined, we demonstrate that phosphatidic acid (PA) elevates its sialidase activity 4 to 5 times at 50 μM in vitro at neutral pH and promotes translocation to the cell surface and cell migration through Ras‐signaling in HeLa and COS‐1 cells. NEU3 was found to interact selectively with PA as assessed by phospholipid array, liposome coprecipitation, and ELISA assays and to colocalize with phospholipase D (PLD) 1 in response to epidermal growth factor (EGF) or serum stimulation. Studies using tagged NEU3 fragments with point mutations identified PA‐ and calmodulin (CaM)‐binding sites around the N terminus and confirmed its participation in translocation and catalytic activity. EGF induced PLD1 activation concomitantly with enhanced NEU3 translocation to the cell surface, as assessed by confocal microscopy. These results suggest that interactions of NEU3 with PA produced by PLD1 are important for regulation of transmembrane signaling, this aberrant acceleration probably promoting malignancy in cancers.—Shiozaki, K., Takahashi, K., Hosono, M., Yamaguchi, K., Hata, K., Shiozaki, M., Bassi, R., Prinetti, A., Sonnino, S., Nitta, K., Miyagi, T. Phosphatidic acid‐mediated activation and translocation to the cell surface of sialidase NEU3, promoting signaling for cell migration. FASEB J. 29, 2099‐2111 (2015). www.fasebj.org